Innovative disk and helical fin designs for thermohydrodynamic enhancement of minichannel heat sinks - Mohammad Mehdi Ahmadi Ashrafi; Seyed Mohammad Javad Hosseini; Ali Akbar Ranjbar; Younes Pahamli; Rasool Bahrampoury (Case Studies in Thermal Engineering)
This study investigates the thermohydrodynamic properties of a heat sink featuring two distinct fin designs: disk fins and helical pin fins. The research focuses on the impact of the number of disks and helices in the helical pin fin configuration on the thermal efficiency of the heat sink. The study considered output parameters, including the Nusselt number, friction factor, and thermal performance coefficient. By examining the heat sink equipped with disk pinfins, it was found that the configuration featuring two disks produced the most favorable results in terms of the Nusselt number, friction coefficient, and thermal performance coefficient. Notably, the utilization of two disk pinfins resulted in a 40 % increase in the thermal performance coefficient compared to the simple heat sink. The research demonstrated that in heat sink with helical pinfins, an increase in the number of helices resulted in corresponding improvements in the Nusselt number, friction factor, and thermal performance coefficient. The most substantial enhancement in thermal performance was observed in the heat sink with six helics, demonstrating a remarkable 98 % increment in comparison to the simple heat sink.